Patterns among micronekton communities in relation to environmental conditions at two shallow seamounts in the south-western Indian Ocean - Annasawmy, Pavanee Angelee (Department of Biological Sciences, 2020)
Seamounts are ubiquitous topographic features across all ocean basins. They rise steeply through the water column from abyssal depths. Depending on their size, shape and summit depths, seamounts reportedly have an influence on the physical flow regimes which may promote the aggregation of zooplankton, micronekton, and top predators above or in the immediate vicinity of their summits. Micronekton form a key trophic link between zooplankton and top marine predators, and are divided into the broad categories: crustaceans, cephalopods and mesopelagic fishes. The vertical and horizontal distributions, assemblages and trophic relationships of micronekton were investigated at two shallow seamounts of the south-western Indian Ocean. La Pérouse is a steep bathymetric feature rising from a deep seabed located at 5000 m and with a summit depth at ~60 m below the sea level. This seamount is located at the north-western periphery of the oligotrophic Indian South Subtropical Gyre province. A seamount to the south of Madagascar, named “MAD-Ridge” in this study, has a summit depth at ~240 m below the sea level and rises from a base at ~1600 m. MAD-Ridge is located within an “eddy corridor” within the productive East African Coastal Province. The micronekton acoustic densities were greater at MAD-Ridge relative to La Pérouse, in accordance with the difference in productivity between the two sites. Physical processes within the cyclonic mesoscale eddy sampled during the MAD-Ridge cruise led to enhanced micronekton acoustic densities in the eddy relative to the MAD-Ridge seamount. While the shallow scattering layer (0-200 m) consisted of common oceanic micronekton species, the summits and flanks of La Pérouse and MAD-Ridge both showed presence of resident or seamount-associated fish species during day and night. Micronekton were also shown to exhibit a range of migration strategies such as diel vertical migration, mid-water migration and no diel migration. However, despite the differing productivity between both pinnacles, crustaceans, smaller-sized squids and mesopelagic fishes exhibited trophic levels ranging from 3 to 4 at both seamounts. This thesis highlights important knowledge gaps on seamount ecosystems and ecological patterns associated to shallow pinnacles. It also underlines the importance of studying seamount ecosystems of the south-western Indian Ocean in order to promote management and conservation measures for a sustainable use of such specific environments.